Нужно воспользоваться формулой разности квадратов практически во всех примерах: (a - b)(a + b) = a² - b².
Выполните умножение:
1) 5b(b - 1)(b + 1) = 5b(b² - 1) = 5b³ - 5b;
2) (c + 2)(c - 2) · 8c² = (c² - 4) · 8c² = 8c⁴ - 32c²;
3) (m - 10)(m² + 100)(m + 10) = (m - 10)(m + 10)(m² + 100) =
= (m² - 100)(m² + 100) = m⁴ - 10 000;
4) (a² + 1)(a² - 1)(a⁴ + 1) = (a⁴ - 1)(a⁴ + 1) = a⁸ - 1;
Упростите выражение:
1) (x + 1)(x - 1) - (x + 5)(x - 5) + (x + 1)(x - 5) = x² - 1 - (x² - 25) + x² - 5x + x - 5 = x² - 1 - x² + 25 + x² - 4x - 5 = x² - 4x + 19;
2) 81a⁸ - (3a² - b³)(9a⁴ + b⁶)(3a² + b³) = 81a⁸ - (3a² - b³)(3a² + b³)(9a⁴ + b⁶) = 81a⁸ - (9a⁴ - b⁶)(9a⁴ + b⁶) = 81a⁸ - (81a⁸ - b¹²) = 81a⁸ - 81a⁸ + b¹² = b¹².
Объяснение:
https://tex.z-dn.net/?f=%20%5Csqrt%7B11-4%20%5Csqrt%7B7%7D%7D%2B%20%5Csqrt%7B16-6%20%5Csqrt%7B7%7D%7D%3D%20%5Csqrt%7B7-2%2A2%20%5Csqrt%7B7%7D%2B4%7D%2B%5Csqrt%7B9-2%2A3%2A%5Csqrt%7B7%7D%2B7%7D%3D%20%5C%5C%20%3D%5Csqrt%7B%28%5Csqrt%7B7%7D%29%5E2-2%2A2%20%5Csqrt%7B7%7D%2B2%5E2%7D%2B%5Csqrt%7B3%5E2-2%2A3%2A%5Csqrt%7B7%7D%2B%28%5Csqrt%7B7%7D%29%5E2%7D%3D%20%5C%5C%20%3D%5Csqrt%7B%28%5Csqrt%7B7%7D-2%29%5E2%7D%2B%5Csqrt%7B%283-%20%5Csqrt%7B7%7D%29%5E2%7D%3D%7C%5Csqrt%7B7%7D-2%7C%2B%7C3-%20%5Csqrt%7B7%7D%7C%3D%20%5C%5C%20%3D%5Csqrt%7B7%7D-2%2B3-%20%5Csqrt%7B7%7D%3D1
Это ссылка!